The Influence of Principal's Leadership and Teacher Professionalism on the Quality of Learning in Elementary Schools - Agung, Fitriyani; Riswandi, Riswandi; Perdana, Ryzal (FKIP Universitas Lampung, 2023)
This study aims to: 1) determine the influence of the principal's initiative on the nature of learning in SD Cluster Mawar Kecamatan Kotabumi (2) determine the effect of the instructor's impressive skills on the nature of learning at SD Cluster Mawar, Kotabumi sub-district (3) examine the impact between the authority of the principal and the extraordinary skills of educators together on the nature of learning at SDN Cluster Mawar Kotabumi District. This study used a quantitative descriptive method and ex post facto approach. Using the Slovin formula, the study sample included 67 people out of a total population of 198 people. The study involves a probability procedure to examine the data, specifically the group evidence. The data analysis involves collecting data through questionnaires and documentation, and multiple and direct linear regression formulas are used. Results show a significant influence between principal initiative and instructor impressive skills on learning quality and between principal leadership and instructor skills on learning quality. To improve the quality of learning, collaborative efforts between the principal's administration and teachers' professional skills must be enhanced.Keywords: Leadership, Learning Quality Principal, Teacher ProfessionalismDOI: http://dx.doi.org/10.23960/E3J/v6i1.97-103